Les silences du droit pénal : une mécanique du chaos ? - Djoheur Zerouki (Criminocorpus)
As a result of the various amnesty laws passed in Algeria, criminal law has been particularly silent on colonial crimes. However, the amnesty instituted at the end of the Algerian war is not an amnesty like any other, either in its implementation or in its philosophy. Bypassing constitutional requirements, the executive used the law on special powers (the state of emergency) as a basis for derogatory measures that were to become a permanent part of the post-colonial normative apparatus, thus achieving the political feat of a veritable "self-amnesty". It is therefore difficult to claim that the amnesty in Algeria was an instrument for ending a cycle of revenge by reconciling the victors and the vanquished, as it is traditionally supposed to be. The executive, by constructing its own amnesty through that of the forces of law and order that it commanded, thus distorted the philosophy of the mechanism intended to organise a return to social peace. By guaranteeing impunity for the perpetrators of colonial crimes, the amnesty established a total omerta and made it impossible to trace the chains of command. The stifling of criminal law gagged the victims of the conflict, understood in the broadest sense to include not only individuals but also Algerian and French societies, which were forced to build their own societies without language or memory. The Criminal Division was not to be outdone, since a few years later, by refusing - in essence - to classify the torture committed during the Algerian war as crimes against humanity, it definitively closed the door on repression and kept them within the bounds of amnesty and the statute of limitations. But "amnesty", says Ricoeur, "as institutional oblivion, touches [...] on the deepest and most concealed relationship with a forbidden past. The more than phonetic, even semantic proximity between amnesty and amnesia points to the existence of a secret pact with the denial of memory that [...] in truth distances it from forgiveness after having proposed its simulation". Moreover, as Karima Lazali writes, "the part of history that is denied by politics is passed down from generation to generation, creating psychological mechanisms that keep the subject ashamed of his or her existence. The emancipation of the subject requires the liberation of the collective, which is also structured around the law and its narrative.